One-stage tracheostomy during surgery reduced early pulmonary infection and mechanical ventilation length in complete CSCI patients - Sun, Lin; Feng, Haoyu; Mei, Jun; Wang, Zhiqiang; Deng, Chen; Qin, Zhixin; Lv, Junqiao (Frontiers in Surgery, 2023)
Objective： Complete cervical spinal cord injury (CSCI) is a devastating injury that usually requires surgical treatment. Tracheostomy is an important supportive therapy for these patients. This study intended to evaluate the early effectiveness of one-stage tracheostomy during surgery compared with necessary tracheostomy after surgery and to identify the clinical factors for one-stage tracheostomy during surgery in complete CSCI patients. Design： Data from 41 patients with complete CSCI treated with surgery were retrospectively analyzed. Participants and Interventions：Ten patients (24.4%) underwent one-stage tracheostomy during surgery, thirteen (31.7%) underwent tracheostomy when necessary after surgery, and eighteen (43.9%) did not have a tracheostomy. Main Results: One-stage tracheostomy during surgery significantly reduced the development of pneumonia at 7 days after tracheostomy, increased the PaO2, and decreased the length of mechanical ventilation, length of stay (LOS) in the intensive care unit (ICU), hospital LOS and hospitalization expenses compared with necessary tracheostomy after surgery. A high neurological level of injury (NLI) (NLI C5 and above), a high PaCO2 in the blood gas analysis before tracheostomy, severe breathing difficulty, and excessive pulmonary secretions were the statistically significant factors for one-stage tracheostomy during surgery in the complete CSCI patients, but no independent clinical factor was found. Conclusions: In conclusion, one-stage tracheostomy during surgery reduced the number of early pulmonary infections and the length of mechanical ventilation, ICU LOS, hospital LOS and hospitalization expenses, and one-stage tracheostomy should be considered when managing complete CSCI patients by surgical treatment.